Ion exchange resin catalyzed reactions-An overview - Bhandari, V. M.; Sorokhaibam, L. G.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
This chapter gives an overview of ion exchange resins as catalyst for a variety of reactions. Emphasis is placed on the use of resin as a catalyst rather than on reactions. Various aspects of resin catalysis, such as types of reactions where resin can be used, the physical form of resin and activity, and issues pertaining to its application as a catalyst are discussed. Advantages and disadvantages of resins as catalyst for different types of reactions are highlighted. Aspects like reactor configurations, selection of resin, process integration, process separations and the environmental impact of using resins as catalysts are also included. Possible future developments in the ion exchange catalysis area are also highlighted.